2011
DOI: 10.1021/ml200163b
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Pharmacokinetics through Manipulation of Physicochemical Properties in a Series of HCV Inhibitors

Abstract: A novel series of HCV replication inhibitors based on a pyrido[3,2-d]pyrimidine core were optimized for pharmacokinetics (PK) in rats. Several associations between physicochemical properties and PK were identified and exploited to guide the design of compounds. In addition, a simple new metric that may aid in the prediction of bioavailability for compounds with higher polar surface area is described (3*HBD-cLogP).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…The predicted values of polar surface area (PSA) for the test ligands, conessine, kurchessine, isoconessimine, pubescine, holadienine, holanamine, conessimine, holadysenterine, kurchine, and loperamide, were 6.03, 5.76, 15.09, 50.49, 16.93, 39.05, 14.99, 74.72, 15.09, and 34.51 Å 2 , respectively ( Table 3 ). Lazerwith et al (2011) [ 55 ] reported that the PSA value of a compound has an inverse relationship with its lipid permeation capability. If the polar surface area (PSA) value of a drug is greater than 140 Å 2 , and HBA > 10, HBD > 5, and MW > 500, in that case it is quite likely that it (the drug) will have a limited cell membrane permeability [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The predicted values of polar surface area (PSA) for the test ligands, conessine, kurchessine, isoconessimine, pubescine, holadienine, holanamine, conessimine, holadysenterine, kurchine, and loperamide, were 6.03, 5.76, 15.09, 50.49, 16.93, 39.05, 14.99, 74.72, 15.09, and 34.51 Å 2 , respectively ( Table 3 ). Lazerwith et al (2011) [ 55 ] reported that the PSA value of a compound has an inverse relationship with its lipid permeation capability. If the polar surface area (PSA) value of a drug is greater than 140 Å 2 , and HBA > 10, HBD > 5, and MW > 500, in that case it is quite likely that it (the drug) will have a limited cell membrane permeability [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…3). Lazerwith et al (2011) [55] reported that the PSA value of a compound has an inverse relationship with its lipid permeation capability. If the polar surface area (PSA) value of a drug is greater than 140 Å 2 , and HBA > 10, HBD > 5, and MW > 500, in that case it is quite likely that it (the drug) will have a limited cell membrane permeability [56].…”
Section: Admet Predictionmentioning
confidence: 99%
“…Finally, the authors concluded that the measurement of compound PSA was not sufficient to correctly evaluate the bioavailability of each HCV replication inhibitor. The weighted combination of hydrogen bond donor count and cLogP was found to be a better predictor of bioavailability for the moderately high PSA compounds (Scheme 47) [51].…”
Section: Antiviral Agentsmentioning
confidence: 99%
“…35 According to their report, not only lipophilicity (C log P) but also HBDs count is an important factor for the prediction of bioavailability in high polarity compounds, and they found 3 ⁄ HBD-C log P as a new metric. Reported high polarity compounds (PSA: 140-160) with acceptable bioavailability (%F rat >20) showed 3 ⁄ HBD-C log P <6.…”
Section: 3mentioning
confidence: 99%